Role of sex on the efficacy of pharmacological and non-pharmacological treatment of heart failure with reduced ejection fraction: A systematic review - Sanromán Guerrero, María Ascensión; Antoñana Ugalde, Sonia; Hernández Sánchez, Elena; del Prado Díaz, Susana; Jiménez-Blanco Bravo, Marta; Cordero Pereda, David; Zamorano Gómez, José Luis; Álvarez-García, Jesús (Frontiers in Cardiovascular Medicine, 2022)
Background: Heart Failure (HF) is a growing epidemic with a similar prevalence in men and women. However, women have historically been underrepresented in clinical trials, leading to uneven evidence regarding the benefit of guideline-directed medical therapy (GDMT). The aim of this review is to outline the sex-differences in efficacy of pharmacological and non-pharmacological treatment of HF with reduced ejection fraction (HFrEF). Methods and Results: We conducted a systematic review via Medline from inception to December 31, 2021 including all randomized clinical trials published in English including adult patients suffering HFrEF that reported data on efficacy of each drug. Baseline clinical characteristics, primary outcome and sex-specific effect are summarized in tables. The systemic review has been conducted in accordance with the preferred Reporting items for systematic Reviews and Metanalyses (PRISMA) statement. 29 articles were included in the systematic review. We observed that the proportion of women enrolled in clinical trials was generally low, the absence of a prespecified analysis of efficacy by sex was frequent, and the level of quality of evidence on efficacy of GDMT and implantable cardioverter defibrillator or cardiac resynchronization therapy in women was relatively poor. Conclusions: Sex influences in the response to treatment of patients suffering HFrEF. All results from the landmark randomized clinical trials are based on study populations composed mainly by men. Further studies specifically designed considering sex-differences are warranted to elucidate if GDMT and new devices are equally effective in both sexes.